Optimizing juvenile sea bass (Lates calcarifer) survival during simulated transport using propack tablets and varying densities - Putra, Dedi Fazriansyah; Fadilla, Raissa; Nurfadillah, Nurfadillah; Suratno, Suratno (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Sea bass (Lates calcarifer) is a commercially important species with high economic value in both domestic and international markets. However, a major challenge in its aquaculture lies in the high mortality rate of fry during transport, primarily due to water quality deterioration and stress-induced responses. To mitigate these effects, the use of water-conditioning agents such as Propack tabletscomprising calcium oxide, zeolite, and clayhas been proposed. This study aimed to evaluate the effect of varying stocking densities on the survival and behavioral response of sea bass fry during 30-hour closed-system transport with Propack tablet supplementation. The experiment was conducted on May 17, 2024, at the Faculty of Marine and Fisheries, Syiah Kuala University, employing a completely randomized design (CRD) with five treatments and four replicates: P0 (50 fish, no Propack), P1 (50 fish + 50 ppm Propack), P2 (65 fish + 50 ppm), P3 (80 fish + 50 ppm), and P4 (95 fish + 50 ppm). The fry used were 56 cm in length. ANOVA results indicated that Propack tablets significantly influenced (P 0.05) the survival rate across densities. The highest survival rate (78.5%) and best behavioral response were observed in P1, indicating the efficacy of Propack tablets at lower densities in maintaining physiological stability during transport.Keywords:Sea bassPropack tabletsDensitySurvival rate